Philippines 2007 Regional Study on Smoking in Girls and Young Women - Sarmiento, Chona Q. (JPAIR Multidisciplinary Research, 2008)
The 2007 Philippines Regional Survey on Smoking in Girls and Young Women provides updated information on women and young girls’ smoking experiences and behaviors, awareness of smoking bans and advertisements, attitudes and beliefs about smoking, and the smoking prevalence and behavior of their family members. A cross-sectional survey was conducted for Phase I and a qualitative study for Phase II, involving 3,000 respondents from 15 schools and 14 colleges in Manila and Zamboanga. Quantitative findings revealed a 37.8% prevalence of respondents who had ever smoked cigarettes, with 18.7% being current smokers, and 60.3% first trying smoking at age 18 or older. Qualitative results highlighted mixed tobacco promotions in the country, weak enforcement of penalty measures, and widespread cigarette access despite high awareness of anti-smoking messages. Tobacco advertisements continue to target young girls and women effectively. The study suggests promising counter-strategies, including stricter sanctions for violators of smoking policies, enhanced media campaigns on smoking’s adverse effects, and health programs focused on intervention and education. Recommendations emphasize forging strong community-school partnerships, initiating teacher training programs, and implementing monitoring systems in schools to prevent smoking among young people. Additionally, there is a need for more empirical evidence on penalties for policy violations and pictorial health warnings on cigarette packs to curb smoking prevalence effectively